APLIKASI AUGMENTED REALITY BAHASA ISYARAT SEBAGAI MEDIA PEMBELAJARAN MENGENAL BAHASA ISYARAT SIBI DENGAN METODE BASED MARKER MULTI TARGET BERBASIS ANDROID - I Made Bayu Krisna Yudha; Royana Afwani; Ahmad Zafrullah M. (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
Sign Language is a communication tool used by deaf students, apart from just using body language. Both sides shouldget the same knowledge of the language used, in this case, namely the Indonesian Sign Language System (SIBI). SIBI isstill very difficult for many deaf students to master, although SIBI has been applied to special schools throughoutIndonesia. The image is difficult to understand, and the SIBI structure tends to be more complicated. Augmented Reality(AR) is one of the technologies appropriate to realize the learning media. With AR technology, learning SIBI code is nolonger rigid and just an image; using 3D objects, you get features like a virtual instructor. This application was testedusing Blackbox and User Acceptance Testing (UAT) methods. Blackbox testing states that target image detection can beperformed optimally at a minimum distance of 10 cm to 80 cm. optimal detection can be achieved if only the targetimage is 1/4 block. UAT testing method shows 88% of users agree the application has met the system aspect, 87% agreethe application has met the user aspect, and 88% agree the application has met the interaction aspect.